Do Mental Health First Aid™ courses enhance knowledge?. Issue 2 (13th March 2017) - Morrissey, Hana; Moss, Simon; Alexi, Nektarios; Ball, Patrick
Abstract : Purpose: Biased assumptions and unhelpful tendencies in human nature can lead people who are experiencing mental illness to shun help and support. Mental illness is often perceived as immutable and/or a sign of weakness. Even those seeking support may not receive the assistance they need. Advice may be unsuitable or people feel too nervous and challenged to help. The Mental Health First Aid™ courses, like general first aid, are designed to enhance community knowledge and thereby support appropriate assistance. The purpose of this paper is to evaluate the extent to which this is achieved. Design/methodology/approach: An educational audit based upon a short quiz administered anonymously to 162 tertiary students from a range of disciplines, before and after delivery of the standard 12 hour Mental Health First Aid™ course. This was used to examine assumptions and proposed actions before and after training. Findings: Analysis of the 162 responses found that the Mental Health First Aid™ courses significantly improve knowledge. This has the potential to increase understanding and support for those suffering mental illness. Research limitations/implications: This educational audit looked only at knowledge improvement. Whether this really does translate into improved outcomes requires further investigation. Practical implications: Tertiary students who are enrolled in health courses and others which involve human interaction as provision of services will be empowered with skills that enable them to interact with those who they will be serving at well-informed level and equity. Social implications: Social inclusion and de-stigmatising mental health issues Originality/value: Mental health first aid courses potentially enable individuals who are not otherwise involved in mental health to assist people in need.